Is Supplier Social Sustainability Vital for Supplier's Financial and Social Performance? Analyzing Mediating Role of Firm Reputation in Thailand - Luedech Girdwichai; Chutikarn Sriviboon (International Journal of Supply Chain Management, 2019)
Purpose: This study signifies the relationship between social sustainability of suppliers and its impact of supplier’s financial and social performance. It also focuses on the supplier firm reputation and the role it plays between sustainability and performance. Methodology: Using survey method, a questionnaire has been developed by past studies and a group of experts and academics. In depth interviews were also conducted from managers related to social sustainability to develop constructs for the survey. The data was collected from the key managers of manufacturing firms in Thailand. After passing through reviewing process, the final sample size came out to be 304. The data collected was then analyzed by using various statistical tools including SPSS and AMOS. Findings: The results of this research reveal that there exist a significant positive association between supplier social sustainability and performance levels. The findings clearly state that financial and social performance of suppliers have strong relationship with the social sustainability practices. It also signifies the mediation role of firm reputation among supplier sustainability and supplier performance levels. Implications: This study provides both theoretical and practical implications. It is considered as an extension in literature related to supplier social sustainability and its performance with the mediating roles of supplier firm reputation. It also allows managers to focus on their strategic decisions in order to develop socially sustainable supply chains to attain competitive edge. Originality: With the rapidly increasing trends of sustainability, limited research has been found on the significance level of this emerging issue. Therefore, this study provides awareness while emphasizing the importance of some major aspects of supplier social sustainability integrated into the supply chain management of manufacturing firms in Thailand.